Advancing College Success Using a Transition Model - Musamali, Kennedy (Advances in Social Sciences Research Journal, 2019)
While 50 years of research has increased our knowledge and understanding of retention, improvements in college completion have remained marginal. Nearly half of the high school students who enter postsecondary institutions do not graduate from college and dropout within the first two years. Many students who fail to graduate drop out after completing three-quarters of their degree program. Studies show that students chose to stay, change, or drop out of their courses at transition points of the college education lifecycle. This paper examines the challenges to college completion and proposes an integrated model to leverage transitions for college success.